The genus Ficus (Moraceae) in the state of Morelos, Mexico - Piedra-Malagón, Eva María; Ramírez Rodríguez, Rolando; Ibarra-Manríquez, Guillermo (Instituto de Ecología, A.C., 2006)
The genus Ficus (Moraceae) is a typical component of tropical areas of our planet. The Mexican species of this taxon are found practically in all country, occurring in several of their habitats. Based on the revision of floristic and taxonomic literature, herbarium specimens deposited in ENCB, HUMO, MEXU, MORE, UAMIZ, and field explorations, a floristic study of the species of Ficus in Morelos state is presented. We recognize eight native species: two belong to subgenus Pharmacosycea (Ficus insipida Willd. and F. maxima Mill.) and six are included in subgenus Urostigma (F. cotinifolia Kunth, F. glycicarpa (Miq.) Miq., F. pertusa L.f., F. petiolaris Kunth, F. trigonata L., and Ficus sp.). The study contains an identification key to taxonomic levels of subgenus and species. We offer also for each species a description with detailed morphological information, photographs, and data over their distribution, habitat, phenology, and uses.